The Frequency of Hypothyroidism in Middle Aged Women Suffering From Headache in Diyala Governorate - Zeina F Fuad; Mohammed M Kamil; Noor M Abdulkader (Diyala Journal of Medicine, 2018)
Background:The previous researches show that the hypothyroidism occurs in approximately 1–2% of women and 0.1% of men and is characterized by a TSH level above the normal reference range and a T4 level below the reference range. This percentage indicate that: women have ten times the risk of hypothyroidism as men, with the difference became significant above the age of 34 years. Hypothyroidism may very easily be missed due to the similarity between the symptoms of hypothyroidism and that of menopause.Many middle-age women complained from headache whether it is tension headache or migraine and since headache is one of the symptoms of hypothyroidism, so there will be many cases of misdiagnosed hypothyroidism. This study estimates thyroid function test for those women to shed a light for the frequency of hypothyroid women.